Photocatalytic remediation of organic waste over Keggin-based polyoxometalate materials: A review - Lai, Sin Yuan (Elsevier Ltd, 2021)
Photocatalytic remediation of industrial water pollution has courted intense attention lately due to its touted green approach. In this respect, Keggin-based polyoxometalates (POMs) as green solid acids in photocatalytic reaction possess superior qualities, viz. unique photoinduced charge-transfer properties, strong photooxidative-photoreductive ability, high chemical and thermal stability, and so forth. Unfortunately, it suffers from a large bandgap energy, low specific surface area, low recoverability, and scarce utilization in narrow absorption range. Therefore, the pollutant degradation performance is not satisfactory. Consequently, multifarious research to enhance the photocatalytic performance of Keggin-based POMs were reported, viz. via novel modifications and functionalizations through a variety of materials, inclusive of, inter alia, metal oxides, transition metals, noble metals, and others. In order to advocate this emerging technology, current review work provides a systematic overview on recent advancement, initiated from the strategized synthetic methods, followed by hierarchical enhancement and intensification process, at the same time emphasizes on the fundamental working principles of Keggin-based POM nanocomposites. By reviewing and summarizing the efforts adopted global-wide, this review is ended with providing useful outlooks for future studies. It is also anticipated to shed light on producing Keggin-based POM nanocomposites with breakthrough visible- and solar-light-driven photocatalytic performance against recalcitrant organic waste.